Difficult Compassion: Chantal Maillard: La compasión difícil. Barcelona: Galaxia Gutenberg, 2019. 218 pp. - Orellana García, Ana; Lagos Gonzalez, Regina; Román Cañamero, Paula (Analysis. Journal of Philosophical Research, 2020)
Review of: Chantal Maillard, La compasión difícil. Barcelona: Galaxia Gutenberg, 2019. 218 pp.